Model of Communication Family Functioning Among Generation Z Families - Alya Denisa; Maulana Rezi Ramadhana (Riviera Publishing, 2026)
This study examines family communication functioning among Generation Z families in the digital era by exploring how communication patterns and family functioning are negotiated in everyday family life. Drawing on the McMaster Model of Family Functioning and Family Communication Patterns Theory, this study employs a qualitative design to capture the lived experiences of Generation Z. Data were collected through in-depth interviews with ten informants and analyzed using thematic analysis through data reduction, open coding, axial coding, and theme development. The findings show that family communication among Generation Z is characterized by a hybrid pattern integrating dialogic interaction with hierarchical family structures. While Generation Z members are given space to express opinions, key family decisions remain under parental authority. Communication functions effectively for coordination, problem solving, and role negotiation, while emotional expression is selective and context-dependent. Affective involvement and emotional responsiveness are often conveyed through instrumental rather than verbal support. Digital media, especially instant messaging, plays a central role in maintaining family connectedness while shaping emotional boundaries and behavioral control. This study proposes a contextual model of family communication functioning that balances dialogic space, clear role structures, adaptive emotional engagement, and strategic digital communication, contributing to the extension of family communication theory in digitally mediated family contexts.